Analiza psychologicznych aspektów samoregulacji odżywiania się oraz poczucia skuteczności w przestrzeganiu diety w grupie młodych kobiet w wieku 19-22 lata = Analysis of the psychological aspects of eating self-regulation and dieting self-efficacy among young women aged 19-22 years - Obara-Golebiowska, Malgorzata (Journal of Education, Health and Sport, 2016)
Obara-Gołębiowska Małgorzata. Analiza psychologicznych aspektów samoregulacji odżywiania się oraz poczucia skuteczności w przestrzeganiu diety w grupie młodych kobiet w wieku 19-22 lata = Analysis of the psychological aspects of eating self-regulation and dieting self-efficacy among young women aged 19-22 years. Journal of Education, Health and Sport. 2016;6(12):543-551. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.213788 http://ojs.ukw.edu.pl/index.php/johs/article/view/4084 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 20.12.2016. Analiza psychologicznych aspektów samoregulacji odżywiania się oraz poczucia skuteczności w przestrzeganiu diety w grupie młodych kobiet w wieku 19-22 lata Analysis of the psychological aspects of eating self-regulation and dieting self-efficacy among young women aged 19-22 years Małgorzata Obara-Gołębiowska Katedra Psychologii Rozwoju i Edukacji, Wydział Nauk Społecznych Uniwersytet Warmińsko-Mazurski w Olsztynie Department of Psychology of Developement and Education, Social Science Faculty University of Warmia and Mazury in Olsztyn Słowa kluczowe: otyłość, poczucie własnej skuteczności w przestrzeganiu diety, samoregulacja odżywienia się, The Three-Factor Eating Questionnaire. Key words: obesity, dieting self-efficacy, eating self-regulation, The Three-Factor Eating Questionnaire. Streszczenie: Wprowadzenie i cel pracy: Otyłość oraz zaburzenia odżywiania przed ciążą oraz w trakcie ciąży mogą istotnie wpłynąć na pogorszenie zdrowia przyszłych matek oraz ich potomstwa. Celem pracy było zbadanie poziomu oraz wzajemnych powiązań pomiędzy emocjonalnym jedzeniem, utratą kontroli nad jedzeniem, restrykcjami dietetycznymi a poczuciem własnej skuteczności w przestrzeganiu diety wśród młodych kobiet w wieku prokreacyjnym. Materiał i metoda: W badaniu wzięło udział 169 kobiet w wieku od 19 do 22 lat. Do pomiaru zachowań związanych z jedzeniem tj emocjonalnego jedzenia, utraty kontroli nad jedzeniem, restrykcji dietetycznych zastosowano kwestionariusz The Three-Factor Eating Questionnaire-18 (TFEQ-18). Do pomiaru poczucia skuteczności w przestrzeganiu diety zastosowano The Diet Self-Efficacy Scale (DIET-SE). Wyniki: Uśrednione wyniki w zakresie poszczególnych podskali kwestionariusza TFEQ-18 oraz w zakresie skali mierzącej poczucie skuteczności w przestrzeganiu diety DIET-SE i poszczególnych jej podskali były na poziomie umiarkowanym. Uzyskano istotne korelacje p<0.01 pomiędzy podskalą brak kontroli nad jedzeniem TFEQ (U), podskalą jedzenie pod wpływem emocji TFEQ (E) oraz podskalą ograniczenia jedzenia TFEQ (R) a całą skalą DIET-SE oraz jej podskalami - wysokokaloryczne jedzenie DIET-SE (HCF), negatywne wydarzenia emocjonalne DIET-SE (NEE) oraz czynniki społeczne i wewnętrzne DIET-SE (SIF). Wnioski: Due to the impact of health and nutrition of mothers on the health of future offspring it is important to define behaviors that predispose to the development of overweight, obesity and eating disorders among women of childbearing age. It is important to allow them to participate in educational, preventive and psychotherapeutic programs taking into account the psychological aspects of eating. Summary: Introduction and aim of the study: Obesity and eating disorders before pregnancy and during pregnancy may significantly worsen the health of mothers and their offspring. The aim of the study was to examine the level of and interrelationships between emotional eating, loss of control over eating, dietary restrictions and dieting self-efficacy among young women in the reproductive age. Material and Methods: The study included 169 women aged 19 to 22 years. For the measurement of eating behaviors i.e. emotional eating, loss of control over eating, restriction of dietary questionnaire was used The Three Factor Eating Questionnaire-18 (TFEQ-18). To measure the dieting self-efficacy was used The Diet Self-Efficacy Scale (DIET-SE). Results: The average results for the different subscale questionnaire TFEQ-18 and on the scale measuring dieting self-efficacy DIET-SE and its individual subscale were at a moderate level. Achieved significant correlations p <0.01 between subscale lack of control over eating TFEQ (U) subscale eating emotion TFEQ (E) and subscale reduce food TFEQ (R) and the whole scale DIET-SE and its subscales - high-calorie food DIET-SE ( HCF), negative emotional events DIET-SE (NEE) and social factors and internal DIET-SE (SIF). Conclusions: Due to the impact of health and nutrition of mothers on the health of future offspring is important to define behaviors that predispose to the development of overweight, obesity and eating disorders among women of childbearing age and taking up their programs, educational and preventive and psychotherapeutic taking into account the psychological aspects of eating.